2003
DOI: 10.1063/1.1622443
|View full text |Cite
|
Sign up to set email alerts
|

Engineering carrier confinement potentials in 1.3-μm InAs/GaAs quantum dots with InAlAs layers: Enhancement of the high-temperature photoluminescence intensity

Abstract: We describe an optical study of structures consisting of an InAlAs-GaAs strained buffer layer and an InAlAs-InGaAs composite strain-reducing layer designed to modify the confining potential of 1.3-μm InAs/GaAs quantum dots (QDs). With increasing (decreasing) InAlAs (InGaAs) thickness in the strain-reducing layer grown above the QDs, the integrated photoluminescence (PL) intensity of the QD ground-state transition increases dramatically and the emission wavelength decreases slightly from 1.36 to 1.31 μm. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…This leads to a degradation of the laser performance, notably an increased temperature sensitivity due to thermal carrier escape. Instead of using a conventional InGaAs or GaAs capping layer, an InAlAs-InGaAs combined two-level capping layer has been developed to increase the confinement of the InAs QDs for advanced laser applications [12,13]. Liu et al [12] have demonstrated that the room-temperature ground-state photoluminescence (PL) intensity of 1.3-mm InAs/GaAs QDs is increased substantially, by a factor of approximately 450, when the InAlAs layer thickness was increased from 1.5 to 6.0 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a degradation of the laser performance, notably an increased temperature sensitivity due to thermal carrier escape. Instead of using a conventional InGaAs or GaAs capping layer, an InAlAs-InGaAs combined two-level capping layer has been developed to increase the confinement of the InAs QDs for advanced laser applications [12,13]. Liu et al [12] have demonstrated that the room-temperature ground-state photoluminescence (PL) intensity of 1.3-mm InAs/GaAs QDs is increased substantially, by a factor of approximately 450, when the InAlAs layer thickness was increased from 1.5 to 6.0 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using a conventional InGaAs or GaAs capping layer, an InAlAs-InGaAs combined two-level capping layer has been developed to increase the confinement of the InAs QDs for advanced laser applications [12,13]. Liu et al [12] have demonstrated that the room-temperature ground-state photoluminescence (PL) intensity of 1.3-mm InAs/GaAs QDs is increased substantially, by a factor of approximately 450, when the InAlAs layer thickness was increased from 1.5 to 6.0 nm. A large energy separation between the ground and the first-excited state of 108 meV has been obtained by this growth technique [14].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the electronic energy states of conduction band in the quantum dot and/or dot-in-a-well structure, and hence the detection wavelengths can be modulated by bandgap engineering including the control of quantum dot size, well width, and the location of the dot later in the well. It can be also performed utilizing different barrier layers [10][11][12]. …”
Section: Resultsmentioning
confidence: 99%
“…For technical application it is favorable to achieve single‐photon emission in the short‐wavelength range at even more elevated temperatures. In order to increase the carrier confinement an often reported concept is to sandwich the QDs between additional barriers with a higher band gap . In II–VI materials, the utilization of additional barriers has already resulted in single‐photon emission at room temperature .…”
Section: Introductionmentioning
confidence: 99%